The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1670/18-088
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of a Cryptic Contact Zone between Mitochondrial Clades of the Eastern Red-Backed Salamander, Plethodon cinereus

Abstract: When evolutionarily divergent lineages adjoin their geographic ranges after a period of isolation, myriad outcomes can occur, from population anastomosis to the evolution of reproductive isolation by way of reinforcement. Hybrid zones represent natural experiments that may indicate whether lineages will maintain their evolutionary independence. Here, we report on a hybrid zone in the Eastern Red-Backed Salamander, Plethodon cinereus, a highly abundant and wide-ranging terrestrial salamander found in the northe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 56 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…Waldron et al (2019) found a clinal transition between two of these clades in Ohio, detectable in the mitochondrial cytochrome b gene, but not in the 10 nuclear microsatellite markers used. Waldron et al (2019) suggest two scenarios to explain the discordance between mitochondrial and nuclear data: first the cline could be an artifact of genetic drift or lineage merger and second, that there may yet be a nuclear cline that is outside their sampling transect. The authors note that a genomic study with wider sampling is needed to fully understand the discordance between mitochondrial and nuclear genomes in P. cinereus .…”
Section: (B) Systematics and Geographic Variationmentioning
confidence: 79%
See 1 more Smart Citation
“…Waldron et al (2019) found a clinal transition between two of these clades in Ohio, detectable in the mitochondrial cytochrome b gene, but not in the 10 nuclear microsatellite markers used. Waldron et al (2019) suggest two scenarios to explain the discordance between mitochondrial and nuclear data: first the cline could be an artifact of genetic drift or lineage merger and second, that there may yet be a nuclear cline that is outside their sampling transect. The authors note that a genomic study with wider sampling is needed to fully understand the discordance between mitochondrial and nuclear genomes in P. cinereus .…”
Section: (B) Systematics and Geographic Variationmentioning
confidence: 79%
“…A recent study has identified six phylogeographic clades within P. cinereus, based on both mitochondrial and nuclear genes (Radomski et al, 2020). Waldron et al (2019) found a clinal transition between two of these clades in Ohio, detectable in the mitochondrial cytochrome b gene, but not in the 10 nuclear microsatellite markers used. Waldron et al (2019) suggest two scenarios to explain the discordance between mitochondrial and nuclear data: first the cline could be an artifact of genetic drift or lineage merger and second, that there may yet be a nuclear cline that is outside their sampling transect.…”
Section: (B) Systematics and Geographic Variationmentioning
confidence: 99%
“…These hybridizing contact zones have important effects on the evolutionary dynamics of the hybridizing species and the biodiversity in the area where the contact happens (Wielstra, 2019;Alves de Moura et al, 2020). The hybridization is not always evident for human, which could have even more pervasive consequences for the biology of the species and their conservation (Gómez et al, 2015;Waldron et al, 2019).…”
Section: Discussionmentioning
confidence: 99%